RECALIBRATING FINANCIAL INCLUSION THROUGH FINTECH: THE ROLE OF DIGITAL LITERACY AS A MODERATOR - Dura, Justita; Binti Azham, Nur Azreen Azriana; Aqromi, Nur Lailatul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research aims to examine the role of digital literacy as a moderator in the relationship between financial technology (biometric identification and mobile money) and digital financial inclusion among people with disabilities in East Java. This research uses a cross-sectional design with an analytical and descriptive approach. Data was collected through semi-structured questionnaires from 360 SMEs owned by people with disabilities in East Java. Data analysis was carried out using Pearson correlation and SEM. The research results show that digital literacy has a significant and positive moderating effect on the relationship between financial technology and digital financial inclusion. Biometric identification and mobile money significantly promote digital financial inclusion. These findings emphasize the importance of digital literacy in increasing the adoption of digital financial services, which can expand financial inclusion for vulnerable groups. The implications of this research indicate the need for the East Java government to strengthen digital literacy programs and improve digital infrastructure to support people with disabilities. Financial service providers are advised to expand outreach to the disabled population. Limitations of this study include data only being collected from one area and its cross-sectional design. Further research is recommended to expand regional coverage and use a longitudinal design